Effects of phenylpyruvate on the growth performance and intestinal microbiota in broiler chicken. Issue 5 (3rd September 2022) - Talpur, M. Z.; Peng, W.; Zeng, Y.; Xie, P.; Li, J.; Zhang, H.; Shu, G.; Jiang, Q.
ABSTRACT: 1. The purpose of this study was to see how dietary supplementation with phenylpyruvate affected broiler growth, slaughter performance, gut health microbiota and immunity. This information can be used to develop alternative approaches to antibiotic replacement in modern poultry production and health. 2. A total of 288, one-day-old broiler chickens were randomly assigned to one of four groups (six replicates each replicate has 12 chickens). A control basal diet (NC), basal diet plus antibiotic virginiamycin 15ppm (PC), basal diet plus phenylpyruvate 1 kg/t or 2 kg/t, respectively (LCP and HCP). 3. Results showed that the birds in the PC group had higher ADFI during the first 21 d, and better FCR than the NC group. The HCP-fed group had a higher all-eviscerated ratio than the NC group and less abdominal fat than the birds fed LCP. The birds fed HCP had increased villus length and crypt depth in the ileum compared to the NC group. 4. The bursa index was lower in the HCP group whereas the thymus index was lower in LCP and PC groups. In contrast, birds fed HCP has lower pro-inflammatory cytokine IL-1, as well as lower TLR4. Phenylpyruvate improved number in the Selenomonadaceae, genus Megamonas bacteroides spp., which are known for their beneficial effects on the maintenance of the cell surface structure, regulating aromatic amino acids and Clostridia jejuni- suppressive treatment respectively. 5. It was concluded that phenylpyruvate can be utilised in feed to improve growth performance and positively modulate gut microbiota. However, this was less efficient than antibiotics in improving growth performance, although more efficient in improving productive performance and gut morphology. Moreover, a high dose of phenylpyruvate is more effective than a low dose.